2010
DOI: 10.1159/000271911
|View full text |Cite
|
Sign up to set email alerts
|

Brain Development, Intelligence and Cognitive Outcome in Children Born Small for Gestational Age

Abstract: Intrauterine growth restriction (IUGR) can lead to infants being born small for gestational age (SGA). SGA is associated with increased neonatal morbidity and mortality as well as short stature, cardiovascular disease, insulin resistance, diabetes mellitus type 2, dyslipidemia and end-stage renal disease in adulthood. In addition, SGA children have decreased levels of intelligence and cognition, although the effects are mostly subtle. The overall outcome of each child is the result of a complex interaction bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
3
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(76 citation statements)
references
References 157 publications
4
65
3
4
Order By: Relevance
“…In a review from 2010, de Bie et al showed a subtle but statistically significant decrease in intelligence level and cognitive disabilities in children born SGA, even though different definitions of SGA make comparisons more difficult [10]. Other studies, with smaller cohorts, have shown results similar to ours, with a small but statistically increased risk of poor school performance and lower intelligence levels for children born SGA, but without looking at different levels of SGA within the same population [11, 31-33].…”
Section: Discussionmentioning
confidence: 99%
“…In a review from 2010, de Bie et al showed a subtle but statistically significant decrease in intelligence level and cognitive disabilities in children born SGA, even though different definitions of SGA make comparisons more difficult [10]. Other studies, with smaller cohorts, have shown results similar to ours, with a small but statistically increased risk of poor school performance and lower intelligence levels for children born SGA, but without looking at different levels of SGA within the same population [11, 31-33].…”
Section: Discussionmentioning
confidence: 99%
“…SGA children have poorer school performance and have more emotional, conduct, and attention deficit hyperactivity disorders, although the differences are mostly subtle (de Bie et al, 2010;van Pareren et al, 2004). Adults who were born SGA show no difference in frequency of employment, marital status, or satisfaction with life.…”
Section: Intellectual Consequences and Health-related Quality Of Lifementioning
confidence: 95%
“…It is an endocrine disrupter, causing feminization in male frogs and other species at very low concentrations; 2 it harms immune systems in exposed aquatic wildlife; 3 and exposure to it during pregnancy may increase risks of birth defects and low birth weight in humans. 4,5 Produced by Syngenta, a European chemical company, atrazine is subject to strict regulation that effectively prevents its use in Europe * -but it remains a staple of American agriculture. While the health and environmental effects of atrazine have been researched in depth, there has been only limited analysis of the economic impacts of atrazine use.…”
Section: Would Banning Atrazine Benefit Farmers?mentioning
confidence: 99%